2022
DOI: 10.2174/2666255813999200904114023
|View full text |Cite
|
Sign up to set email alerts
|

Improving Arabic Text Classification Using P-Stemmer

Abstract: Introduction: Stemming is an important preprocessing step in text classification, and could contribute in increasing text classification accuracy. Although many works proposed stemmers for English language, few stemmers were proposed for Arabic text. Arabic language has gained increasing attention in the previous decades and the need is vital to further improve Arabic text classification. Method: This work combined the use of the recently proposed P-Stemmer with various classifiers to find the optimal clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Stopwords account for around 20%-30% of a document's exhaustive words. These terms can be deleted since they are repetitive [28]. The basic approach for extracting stopwords is static, meaning it uses a pre-filled list of all words that are semantically irrelevant to a specific language.…”
Section: Preprocessingmentioning
confidence: 99%
“…Stopwords account for around 20%-30% of a document's exhaustive words. These terms can be deleted since they are repetitive [28]. The basic approach for extracting stopwords is static, meaning it uses a pre-filled list of all words that are semantically irrelevant to a specific language.…”
Section: Preprocessingmentioning
confidence: 99%
“…The author [13] proposes an approach to improve P-Stemmer by combining it with various classifiers such as Naïve Bayes, Random Forest, Support Vector Machines, K-Nearest Neighbor, and K-Star. In this study they used a data set synthesized from various online news pages and did the experience on Weka tools, which is achieving the result showed that the P stemmer has Improved when using NB.…”
Section: Related Workmentioning
confidence: 99%
“…Heuristic techniques have been widely applied to perform data classification tasks [ 32 , 33 ]. A heuristic for one dataset may not be equally effective for another dataset [ 34 ].…”
Section: Related Workmentioning
confidence: 99%